Why technologies often fail to scale: Policy and market failures behind limited scaling of alternate wetting and drying in rice in Bangladesh - Pandey, Sushil; Yadav, Sudhir; Hellin, Jon; Balié, Jean; Bhandari, Humnath; Kumar, Arvind; Mondal, Manoranjan K. (MDPI, 2020)
Rapid expansion of groundwater use for irrigation for dry season rice production in Bangladesh has led to overuse, deterioration of groundwater quality, increased cost of irrigation, and higher greenhouse gas emissions. The divergence between marginal private and social cost of irrigation due to market failures in the presence of these externalities, has resulted in excessive use of groundwater. A combination of policy reforms and improvements in irrigation practices are hence needed to reduce irrigation water use. The paper analyses why an improved irrigation practice, known as “alternate wetting and drying (AWD)” that can potentially reduce irrigation water use substantially, has failed to scale despite widespread testing and promotion in Bangladesh for over a decade. The main reason for this failure to scale is the lack of economic incentives to save water as pricing is based on per unit area irrigated, not on the amount of water used. This paper highlights the dynamics of the water market and pricing in Bangladesh, along with biophysical and social constraints to farmer adoption of AWD. It also proposes changes in policy incentives, new directions for crop and water management research, and institutional reforms for wider adoption of AWD and other water-saving practices.